Struktur Modal, Debt to Equity Ratio (DER), Net Profit Margin (NPM), PT Gudang Garam Tbk - Junaidin Junaidin; Nafisah Nurulrahmatia; Ovriyadin Ovriyadin (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of capital structure, proxied by the Debt to Equity Ratio (DER), on profitability as measured by the Net Profit Margin (NPM) at PT Gudang Garam Tbk during the 2014–2023 period. Capital structure is one of the fundamental aspects of corporate financial management because it is directly related to funding sources, financial risk, and the cost burden borne by the company. The use of an unoptimal composition of debt and equity may lead to a decline in net profit. The data used in this study are secondary data in the form of annual financial statements obtained from the official websites of the Indonesia Stock Exchange (IDX) and PT Gudang Garam Tbk. The analytical method applied is simple linear regression, using SPSS version 26, which aims to determine the partial effect of DER on NPM. The results indicate that capital structure has a positive and significant effect on Net Profit Margin. These findings suggest that appropriate management of capital structure, through a balance between debt and equity usage, can improve operational efficiency and enhance corporate profitability. Therefore, the management of PT Gudang Garam Tbk is advised to continuously evaluate its capital structure proportions to maintain financial stability and improve sustainable net profit performance.